Mashrabiya in Islamic architecture between idea authenticity and applying novelty - Hayam Salama (Journal of Architecture, Art & Humanistic Science, 2019)
Mashrabiya had formed one of the most important elements of architecture specially civil architecture in Islamic heritage. As it is known as a successful architectural solution for climate nature because the shape of its configuration allows it to control sun rays and air currents and forming interior comfortable environment and also providing privacy specially in housing architecture. So Mashrabiya comes in our Islamic heritage with consistency with climate, privacy and culture considerations for the occupants of the interior environment additionally with Aesthetic considerations represented from its infinite design characterized with the elasticity of its formations. The Egyptian carpenter was one of the most handicrafts men who represented Mashrabiya arts with different designs and forms and he excelled at perfection at this kind of art and he represented it to the whole world in the form of beautiful wooden interfaces. Many International architects paid attention to this important architectural element and started taking inspiration from this concept to represent modern solutions for many architectural interface for public and private buildings and they turned this wooden local heritage element to elastic system for natural light responding to high technology and representing Contemporary aesthetic solutions taking its origins from Islamic heritage in consistency with modernization and Contemporary Technology.